Education and regional development - Tilak, Jandhyala B G (New Delhi, India : Yatan Publications, 1986)
With reference to India; contributed articles.
Includes index.
Keywords: Education and state -- India; Education -- India; Regional planning -- India; Education -- India -- Regional disparities